Field Notes. : Working Title Situation #01. - Van Geert, David; Buys, Nele; Leblanc-Bolduc, Dominique (Brussels : Workspace, 2015)
Bakalov, Christian ; Biong, Hedvig, Castilla, Pablo & Hafkenscheid, Niko ; Butkute, Ruta ; Campbell, Bryan ; Eliceche, Cecilia Lisa ; Etrange Miroir ; Heremans, Roel ; Lee, Dongyoung ; Michalakopoulou, Antigone ; Nature Theatre of Oklahoma ; Pichat, Fabrice ; Rabreau, Diane ; Sanchis, Salva ; Sobarzo, Rodrigo ; Steur, Nico ; Tijskens, Myriam ; Vandewalle, Benjamin ; Vervloessem, Gosie ; Wouters, Jozef & Peeters, Jeroen ; Annerel, Stefan ; Bartolini, Massimo ; Bouckaert, Charlotte . Van Herreweghe, Egon ; Vogel, Anna
Event by Workspace Brussels, Kaaistudios & Les Brigittines, Brussels, 18.06.2015 - 20.06.2015.
Engels
boek